Supreme and Constitutional Court’s Decisions on Permission of Ex-Corruptors to be Parliamentary Candidates : Whose Rights Should be Protected ? - Susmayanti, Riana; Hidayat, Fitri (Brawijaya Law Journal, 2025)
Along with the trend of many Parliamentary members being caught in corruption, Law No. 7/2017 on General Elections apparently allows ex-corruptor to run for or be nominated as Parliamentary members. Parliamentary is an institution that has the legislative power to form laws (including the Anti-Corruption Law, etc). Allowing ex-corruptors to run for Parliamentary candidate means that the seriousness of this country's fight against corruption is questionable. This study analyzes the permissibility of ex-corruptors to become parliamentary candidates based on KPU Regulation 20/2018 and 31/2018, Law 7/2017, Supreme Court Decision No. 46 P/HUM/2018 and Constitutional Court Decision No. 87/PUU-XX/2022. Moving on from that analysis, this normative juridical research is intended to answer the legal issues : 1) What is the human rights perspective of ex-corruptors regarding on permission of ex-corruptors from running for or being nominated as members of parliament ? and 2) What is the human rights perspective of other citizens regarding on permission of ex-corruptors from running for or being nominated as members of parliament ? Using the case, conceptual and statutory approach, the author aims to show that it is not only the human rights of ex-corruptors that must be protected, but also the human rights of the other citizen to get members of Parliament who are clean from corruption. Some previous studies discuss former corruptors as parliamentary candidates, such as Agus Amelia Virismanda Vantri (2019 and also Andri Yanto and Faidatul Hikmah (2023), but none have examined human rights from the perspective of former corruptors and citizens of other countries. When the author presented this paper at an international conference, it turned out that ex-corruptors becoming parliamentary candidates is also a problem in other countries, making this theme important for foreign readers.